2018
DOI: 10.3892/ol.2018.7835
|View full text |Cite
|
Sign up to set email alerts
|

Association between contrast-enhanced ultrasonography and histopathological findings of the metastatic lymph nodes of patients with head and neck cancer: A preliminary study

Abstract: The present study aimed to investigate the usefulness of contrast-enhanced ultrasonography (CEUS) and a newly developed analysis software for the detection of microcapillary network distribution in lymph nodes of patients with head and neck cancer (HNC) by comparing the CEUS and histopathological findings. Patients that were diagnosed with HNC between February and September 2016 were enrolled. A total of five patients underwent resection of the primary tumor and neck dissection as their initial treatment. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…However, the majority of other metastatic lymph nodes did not show typical internal heterogeneous enhancement combined with peripheral rim-like enhancement in CEUS. Furthermore, studies found that the increase in blood vessel volume and density precedes an increase in lymph node size in the early stages of lymph node metastasis [ 34 ], which has been hypothesized that detection of these changes by CEUS may allow early diagnosis of lymph node metastasis [ 35 ]. It was also reported that metastatic lymph nodes exhibit characteristic enhancement patterns such as centripetal perfusion, and the absence of hilum after enhancement, which were helpful for differential diagnosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of other metastatic lymph nodes did not show typical internal heterogeneous enhancement combined with peripheral rim-like enhancement in CEUS. Furthermore, studies found that the increase in blood vessel volume and density precedes an increase in lymph node size in the early stages of lymph node metastasis [ 34 ], which has been hypothesized that detection of these changes by CEUS may allow early diagnosis of lymph node metastasis [ 35 ]. It was also reported that metastatic lymph nodes exhibit characteristic enhancement patterns such as centripetal perfusion, and the absence of hilum after enhancement, which were helpful for differential diagnosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This software can calculate the density of particles in the drawn figures, which is thought to represent the capillary density of the tumor (Figures 1C and 2C). 12 We measured capillary density rates in tumors.…”
Section: Methodsmentioning
confidence: 99%
“…Sonazoid (Daiichi Sankyo, Tokyo, Japan), a lipid‐stabilized suspension of perfluorocarbon microbubbles, was used in the present study as the ultrasound contrast agent. In Japan, CEUS with Sonazoid is used for the evaluation of liver and mammary gland tumors 12 . The objective of the present study was to evaluate the usefulness of CEUS with Sonazoid for making differential diagnoses between PMAs and WTs.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Although CT, MRI, and PET may be used to recognize abnormal LNs, detection of the nodes measuring <10 mm in diameter can be difficult. 7 US is widely used in evaluation of the number, size, site, shape, matting, and internal architectures of LNs, considering its low cost, easy usage, tolerance by patient, absence of radiation, and its combination with fine needle aspiration cytology (FNAC). 8 As a result of the diversity of causes and similar US images of different pathologies, lymphadenopathy is still a diagnostic challenge for ultrasonography.…”
mentioning
confidence: 99%
“…The color Doppler provides only a rough outline of the LN capillaries, while the CEUS images depict microvascular patterns in the LNs in greater detail. 7 CEUS has been widely used for assessment of lesions in the liver, kidney, pancreas, spleen, ovary, thyroid, breast, and prostate, as well as for identification of sentinel nodes in breast cancer patients. [11][12][13] A meta-analysis on the accuracy of CEUS for diagnosis of superficial metastatic LNs indicated that its sensitivity and specificity were 0.88 (95% CI, 0.83-0.92) and 0.80 (95% CI, 0.74-0.85), respectively.…”
mentioning
confidence: 99%